THE COMPARISON OF THE TAX RATES BETWEEN THE REPUBLIC OF KOSOVO WITH COUNTRIES IN REGION AND THE EUROPEAN UNION COUNTRIES - Imeri, Vehbi (European Scientific Journal, ESJ, 2013)
This paper contains the comparative analysis of some taxes and social security contributions which are of most importance having an impact on the decisions of the investors for investments and opening new jobs and sustainable economical development. This comparison of the tax rates and social insurances is made between the Republic of Kosovo and countries in the region and the European Union countries (Albania, Macedonia, Montenegro, Croatia, Bosnia and Herzegovina and Serbia). The targets of the comparison are tax rates and social securities as follows: 1. The tax on income a) Corporate tax b) Taxed on individual – personal incomes 2. Social security a) Social security paid by employees b) Social security paid by employers c) Health insurance paid by employees d) Health insurance paid by employers e) Health insurance at work f) Social Security from unemployment paid by the employees g) Social Security from unemployment paid by the employers 3. VAT (Value Added Tax)